2016
DOI: 10.1002/biof.1259
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol and cancer metastasis

Abstract: Tumor metastasis involves some of the most complex and dynamic processes in cancer, often leading to poor quality of life and inevitable death. The search for therapeutic compounds and treatment strategies to prevent and/or manage metastasis is the ultimate challenge to fight cancer. In the past two decades, research focus on vitamin E has had a shift from saturated tocopherols to unsaturated tocotrienols (T3). Despite sharing structural similarities with tocopherols, T3 strive to gain scientific prominence du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…TTs (specifically, γ-TT and δ-TT) were widely reported to be associated with significant health benefits in different chronic diseases, based on their neuroprotective, cholesterol-lowering, antioxidant and antiinflammatory activites 27 , 28 . TTs were also shown to possess antitumor activity by suppressing cancer cell proliferation and by increasing the sensitivity of tumor cells to chemotherapeutic agents 29 , 30 . We recently reported that δ-TT exerts a significant proapoptotic activity in human cutaneous melanoma cells (while sparing normal melanocytes), independently on their genetic mutations, by triggering the endoplasmic reticulum (ER) stress prodeath pathways 31 .…”
Section: Introductionmentioning
confidence: 99%
“…TTs (specifically, γ-TT and δ-TT) were widely reported to be associated with significant health benefits in different chronic diseases, based on their neuroprotective, cholesterol-lowering, antioxidant and antiinflammatory activites 27 , 28 . TTs were also shown to possess antitumor activity by suppressing cancer cell proliferation and by increasing the sensitivity of tumor cells to chemotherapeutic agents 29 , 30 . We recently reported that δ-TT exerts a significant proapoptotic activity in human cutaneous melanoma cells (while sparing normal melanocytes), independently on their genetic mutations, by triggering the endoplasmic reticulum (ER) stress prodeath pathways 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cancer prevention, researchers are exploring the therapeutic role of tocotrienols in cancers (7982). Here we present a selection of studies published in this area.…”
Section: Tocotrienols Have Anti-cancer Propertiesmentioning
confidence: 99%
“…Antioxidants have been shown to be of therapeutic benefit in oxidative stress-induced diseases, including DR [18,19]. Since TRF has shown potent antioxidant effects in several human and animal studies [20][21][22][23], it may be of potential therapeutic value against DR. Additionally, some in vitro and in vivo studies have also shown that TRF produces anti-cancer effects due to its anti-angiogenic properties [24]. The anti-angiogenic properties of TRF have been attributed to its ability to suppress several signaling pathways, such as Ras-Raf-MEK-ERK and Fyn/HIF-1a pathways, leading to downregulation of VEGF expression [25].…”
Section: Introductionmentioning
confidence: 99%